Massively Parallel Screening of Toll/Interleukin‐1 Receptor (TIR)‐Derived Peptides Reveals Multiple Toll‐Like Receptors (TLRs)‐Targeting Immunomodulatory Peptides - Yun Lim; Tae Kyeom Kang; Meong Il Kim; Dohyeon Kim; Ji Yul Kim; Sang Hoon Jung; Keunwan Park; Wook‐Bin Lee; Moon‐Hyeong Seo (Advanced Science)
Abstract Toll‐like receptors (TLRs) are critical regulators of the immune system, and altered TLR responses lead to a variety of inflammatory diseases. Interference of intracellular TLR signaling, which is mediated by multiple Toll/interleukin‐1 receptor (TIR) domains on all TLRs and TLR adapters, is an effective therapeutic strategy against immune dysregulation. Peptides that inhibit TIR‐TIR interactions by fragmenting interface residues have potential as therapeutic decoys. However, a systematic method for discovering TIR‐targeting moieties has been elusive, limiting exploration of the vast, unsequenced space of the TIR domain family. A comprehensive parallel screening method is developed to uncover novel TIR‐binding peptides derived from previously unexplored surfaces on a wide range of TIR domains. A large peptide library is constructed, named TIR surfacesome, by tiling surface sequences of the large TIR domain family and screening against MALTIR and MyD88TIR, TIRs of two major TLR adaptor proteins, resulting in the discovery of hundreds of TIR‐binding peptides. The selected peptides inhibited TLR signaling and demonstrated anti‐inflammatory effects in macrophages, and therapeutic potential in mouse inflammatory models. This approach may facilitate the development of TLR‐targeted therapeutics.